Association of dietary inflammatory index on all-cause and cardiovascular mortality in U.S. adults with metabolic dysfunction associated steatotic liver disease - Lin Tao; Tiantian Wu; Xiaoning Du; Qian Li; Yuefei Hao; Tao Zhou; Yinping Yi (Frontiers in Nutrition)
BackgroundsAn inflammatory diet is pivotal in metabolic dysfunction-associated steatotic liver disease (MASLD) development. However, it remains unclear whether Dietary Inflammatory Index (DII), which serves as a reliable indicator to assess pro-inflammatory diet, have associative effects on mortality outcomes of MASLD.MethodsParticipants in the National Health and Nutrition Examination Survey (NHANES) database from 1999 to 2018 years were included. Kaplan–Meier (KM) curves were used to estimate survival probabilities, while Cox regression analysis and restricted cubic splines (RCS) were employed to assess the association between DII and mortality outcomes. The concordance index (C-index) evaluated the accuracy of multivariate-adjusted DII for mortality among MASLD participants.ResultsThe cohort consisted of 4,510 men and 4,323 women with a median age of 52 years. Multivariate-adjusted Cox regression analysis revealed that high levels of DII were significantly associated with the all-cause mortality of participants with MASLD (multivariable-adjusted hazard ratio (aHR) = 1.28, 95% confidence interval (CI) 1.10–1.49, p = 0.002, DII aHR for cardiovascular mortality = 1.28, 95% CI 1.07–1.53, p = 0.006). The C-index for the multivariate model, integrating DII and other clinical variables, was 0.837 for all-cause mortality and 0.860 for cardiovascular mortality. RCS analysis showed a positive linear relationship between DII and all-cause mortality rate (p for nonlinearity = 0.057), with no significant nonlinearity for cardiovascular mortality (p = 0.953). Subgroup analyses indicated stronger associations in participants <65 years, married, with a college education, non-smokers, non-drinkers, and those without hypertension.ConclusionElevated DII levels are linked to higher mortality in adults with MASLD, underscoring the index’s utility in predicting mortality risks. These findings shows that dietary interventions targeted inflammation may be helpful in this population.